Application of the Electronic Module "Promoting Pancasila Student Profiles Through Sports" in Physical Education, Sports and Health (PJOK) Learning - Yuni Fitriyah Ningsih; Advendi Kristiyandaru; Nanik Indahwati; Muchamad Arif Al Ardha (Laksana Olahraga, 2023)
The problem faced by elementary school teachers in Lamongan district is the lack of knowledge about the profile of Pancasila students. This service aims to introduce the profile of Pancasila students through sports, as well as prioritizing "Sports for Development" as an effort to use sports, physical activity, and games as a tool to achieve development goals, and specifically support the Sustainable Development Goals (TPB) of the United Nations -Nation (UN). Therefore, teachers as participants are expected to be able to understand and practically apply the concepts and principles of "Sports for Development" in teaching Physical Education, Sports and Health (PJOK) to develop good values ??and self-competencies for elementary school students. The method used is lectures and training on the profile of Pancasila students through sports in PJOK learning. This activity was carried out in three stages, namely the preparation, implementation, and evaluation stages. As a result of this dedication, the teacher has been able to increase understanding and be able to implement Pancasila student profiles through sports in PJOK learning